2020
DOI: 10.1016/j.tips.2020.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Inhaled RNA Therapy: From Promise to Reality

Abstract: RNA-based medicine is receiving growing attention for its diverse roles and potential therapeutic capacity. The largest obstacle in its clinical translation remains identifying a safe and effective delivery system. Studies investigating RNA therapeutics in pulmonary diseases have rapidly expanded and drug administration by inhalation allows the direct delivery of RNA therapeutics to the target site of action while minimizing systemic exposure. In this review, we highlight recent developments in pulmonary RNA d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 115 publications
(194 reference statements)
0
53
0
Order By: Relevance
“…For example, a murine allergic airway inflammation model has been used for preclinical studies of asthma. However, mice and humans display different distribution of lung inflammation [ 142 ]. (v) Animal models for obstructive airway diseases are developed using various chemical stimuli, e.g., cigarette smoke, allergen, or irritant gas exposures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a murine allergic airway inflammation model has been used for preclinical studies of asthma. However, mice and humans display different distribution of lung inflammation [ 142 ]. (v) Animal models for obstructive airway diseases are developed using various chemical stimuli, e.g., cigarette smoke, allergen, or irritant gas exposures.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to conventional therapeutic approaches using small-molecule drugs, peptides, proteins, and monoclonal antibodies, RNA-based therapy provides additional advantages, including rapid bioinformatics-based design, high selectivity and potency, and the possibility of providing personalized therapy [ 140 , 141 ]. RNA therapeutics include three different classes [ 142 , 143 ]: (i) drugs that inhibit gene expression (e.g., small interfering RNA (siRNA), ASOs, and microRNA (miRNA), Piwi-interacting RNA (piRNAs), long noncoding RNAs (LncRNAs), and circular RNAs (circRNAs)); (ii) protein-encoding drugs (e.g., mRNA); (iii) protein-targeting drugs (e.g., RNA aptamers). The key pathological feature of obstructive airway diseases is the involvement of multiple inflammatory mediators that are often regulated by key genes [ 144 ].…”
Section: Novel Inhaled Medicines For Obstructive Airway Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…While some progress has been made by repurposing the RNA polymerase inhibitor Remdesivir (5) or by ameliorating SARS-CoV-2 induced lung injury using Dexamethason (6), lethality of COVID-19 remains high (7). A promising alternative approach could be to deliver small interfering (si)RNAs (8)(9)(10)(11) to the respiratory tract by inhalation (12) and induce degradation of viral RNAs by the RNA-interference (RNAi) machinery. Studies performed with Severe Acute Respiratory Syndrome Coronavirus-1 (SARS-CoV-1) or Middle East Respiratory Syndrome Coronavirus (MERS-CoV), showed that siRNAs can silence viral RNA and relieve symptoms caused by related coronaviruses (13)(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…While some progress has been made by repurposing the RNA polymerase inhibitor Remdesivir 12 or by ameliorating SARS-CoV-2 induced lung injury using Dexamethason 13 , lethality of COVID-19 remains high 14 . A promising alternative approach could be to deliver siRNAs to respiratory tract by inhalation 15 and induce degradation of viral RNAs by the RNA-interference (RNAi) machinery. Studies performed with SARS-CoV-1 or Middle East Respiratory Syndrome Coronavirus (MERS-CoV), showed that siRNAs can silence viral RNA and relieve symptoms caused by related coronaviruses [16][17][18][19][20] .…”
mentioning
confidence: 99%